Araliaceae endémicas del Perú - León, Blanca (2006)
This family is represented in Peru by six genera and 77 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), mostly shrubs and trees. Here we recognize 28 endemic species in three genera. The systematics of Araliaceae is currently under study, and taxonomic changes and novelties are to be expected (J. Wen, pers. comm.). Endemic Araliaceae are found in the Pluvial Montane Forest, Very Humid Montane, and Humid Lowland Amazonian Forest regions, between 230 and 3640 m elevation. We applied IUCN categories and criteria to 22 species. Only two endemic species have been found in a protected area.